Cell-Free DNA, Neutrophil extracellular traps (NETs), and Endothelial Injury in Coronavirus Disease 2019– (COVID-19–) Associated Acute Kidney Injury - Brandon Michael Henry; Maria Helena Santos de Oliveira; Isaac Cheruiyot; Justin Benoit; James Rose; Emmanuel J. Favaloro; Giuseppe Lippi; Stefanie Benoit; Naomi Pode Shakked (Mediators of Inflammation)
Introduction: Neutrophil extracellular traps (NETs) release (i.e., NETosis) has been recently implicated in the pathomechanism underlying severe end-organ damage in Coronavirus Disease 2019 (COVID-19) and could present a novel therapeutic target. We aimed to determine whether circulating levels of cell-free DNA (cfDNA), a surrogate for NETosis, may be associated with the development of acute kidney injury (AKI), a major contributor to poor outcomes and mortality in COVID-19. Methods: Blood samples were collected prospectively from adult patients infected with SARS-CoV-2 presenting to the emergency department (ED). Circulating levels of cfDNA were quantified from patients’ serum. Further assessment of correlations between cfDNA levels and markers of AKI (i.e., serum creatinine (SCr), cystatin C, neutrophil gelatinase–associated lipocalin (NGAL)), biomarkers of thrombotic microangiopathy and of inflammation in patients’ serum was performed. Results: Fifty-one COVID-19 patients were enrolled. cfDNA levels were found to be significantly higher in those who developed severe AKI (p<0.001) and those needing renal replacement therapy (p=0.020). cfDNA positively correlated with ED SCr, NGAL, cystatin C, neutrophil count, neutrophil-to-lymphocyte ratio, C3a, C5a, Scb5-9, IL-6, IL-8, IL-10, TNF-α, LDH, CRP, ferritin, and fibrinogen and negatively correlated with ADAMTS13/von-Willebrand factor ratio and lymphocyte count. In a multivariate logistic regression, a one-unit increase in cfDNA value was associated with 4.6% increased odds of severe AKI (OR=1.046; p=0.040). Finally, cfDNA significantly correlated with established NETs components, myeloperoxidase, and neutrophil elastase. Conclusion: Intravascular NETosis could be an important contributing factor in the development of microthrombosis and COVID-19-associated AKI. Further research is urgently needed to understand the role of NETosis in COVID-19 and evaluate therapeutic avenues for targeting this process.